Stand-up Commedy sebagai Metode Pembelajaran Metode Penelitian Komunikasi Kualitatif - Rianto, Puji; Sulkhan, Khumaid Akhyat (Universitas Islam Indonesia, 2025)
This study investigated the use of the project-based learning (PBL) method for teaching qualitative communication research methods. This study employed a quasi-experimental design without a control group or pre-treatment measurements. The researcher did not use a pre-test or post-test. Evaluation was conducted using a survey (distributing g-forms) to the experimental class, supplemented by focus group discussions (FGDs). The study showed that the PjBL method contributed to providing students with cognitive knowledge and experience regarding qualitative communication research methods. Furthermore, the PBL method also positively contributed to improving students' collaborative work skills in completing group assignments or projects. The quasi-experimental design does not provide a complete picture of the effectiveness of the PjBL method. Furthermore, this study design did not use a pre-test or post-test. The PBL method can be used as a learning method for qualitative research methods that require research experience. Developing a more detailed project guide and using a control group in the study are highly recommended to explain the effectiveness of this method better.